The Golden Leaf - Unknown (My University, 1961)
Manuscript of the story of Tobacco in Jamaica
The Romance of the Golden Leaf (The story of Tobacco in Jamaica)
11 pgs. Typescript, letter-sized, sepia-toned, fragile condition.
Keywords: Tobacco - Jamaica - History; Tobacco industry - Jamaica; Tobacco industry - Jamaica - History